Adapting to the Era of Change: Optimizing Individual Potential Within the Frame of Islamic Management - Khairunnisak Nasution; Nuri Aslami (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This journal aims to investigate Islamic management concepts and principles that can be used in an effort to optimize individual potential in facing an era of change. In the context of globalization and rapid changes, Islamic management can play an important role by providing a relevant and useful framework for facing challenges in an era of change. This journal provides an analysis of Islamic management principles such as monotheism, trust, endeavor, shura, and tarbiyah and how these principles can be applied to optimize individual potential. In addition to strategies, Islamic management practices and effective strategies in dealing with various obstacles to achieve success in implementing Islamic management in order to optimize individual potential. The application of Islamic management concepts will also have an impact on character building and sustainable success in dealing with change.